Impact of access to ICT on regional economic growth in Kazakhstan (Journal of Economic Research & Business Administration, 2020)
This article examines the impact of access to information and communication technologies (ICT) inorganizations on regional economic growth in Kazakhstan. The main objective of the study is to compareregions with high, medium and low levels of regional development. Data were collected for the period2007-2018 for all 16 regions of the country. Internet access in organizations, the number of computersand landlines were considered as ICT, and the main indicator of regional development was taken as thegross regional product (GRP) of the regions of Kazakhstan. POLS (pooled ordinary least squared) – thecombined least squares method (for panel studies), FE (fixed effects) – the method with fixed effects, RE(random effects) – the method with random effects, and IV (instrumental variables) – the method withinstrumental variables were used to create a regression model with high reliability. The region’s innovationactivity for the number of computers in organizations was adopted as an instrumental variable. Thearticle presents the results of a regression model with the division of regions with high, medium and lowdevelopment and their analysis. In addition, the results were presented for splitting into sub-periods of2007-2013 and 2014-2018 years. Significant differences between groups of regions of Kazakhstan werenot revealed as a result of this study.